Three feathers - Van Camp, Richard 1971- (HighWater Press, 2015)
Explores the power and grace of restorative justice in one Northern community and the cultural legacy that can empower future generations
Cover title
Keywords: Indians of North America -- Comic books, strips, etc; Restorative justice -- Comic books, strips, etc; Graphic novels; Indianer; Ausgleichende Gerechtigkeit; Nordamerika; Comic